Particulate carbonaceous materials and method for separation thereof

Gravity separation and additional processes allow for the selective separation of particulate carbon materials into fractions with varying specific surface areas, enhancing the mechanical properties of rubber products by maintaining particle size distribution homogeneity.

JP2025011234AInactive Publication Date: 2025-01-23SUNCOAL INDS GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024178640
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-04
Filing Date
2024-10-11
Publication Date
2025-01-23
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods are inadequate for selectively separating particulate carbon materials into fractions with different specific surface areas, as they often result in aggregates that cannot be easily distinguished by size or density, limiting their application in high-quality rubber products.

Method used

A method involving gravity separation in liquid or gas phases, combined with additional processes like drying and comminution, allows for the separation of particulate carbon materials into fractions with significantly different specific surface areas, maintaining homogeneity in primary particle size distribution.

Benefits of technology

This method enables the production of more homogeneous fractions with higher specific surface areas, suitable for demanding applications, while maintaining particle size distribution, thus improving the mechanical properties of rubber products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011234000008
    Figure 2025011234000008
  • Figure 2025011234000009
    Figure 2025011234000009
  • Figure 2025011234000010
    Figure 2025011234000010
Patent Text Reader

Abstract

To provide a method for separating more homogeneous fractions of a particulate carbonaceous material, a material obtained by the method, and uses thereof.SOLUTION: Provided is a method for separating a particulate carbonaceous material obtained by hydrothermal carbonization or precipitation of an organic material into at least two fractions, wherein the STSA surface area of the particulate carbonaceous material is at least 5 m2 / g, the first fraction has a STSA surface area greater than the STSA surface area of the particulate carbonaceous material and the second fraction has a STSA surface area less than the STSA surface area of the particulate carbon starting material, and gravity separation of the particulate carbonaceous material is included, and wherein the gravity separation is carried out in an air classifier or a powder separator performed in liquid or gas phase.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for separating particulate carbon materials, the materials obtained thereby, and their uses. [Background technology]

[0002] Particulate carbon materials are used in many applications. These range from use as black dyes to use as fillers in polymers, especially elastomers. Such carbon-based particulate materials, e.g. carbon black, can be materials with a relatively high percentage of carbon. Other particulate carbon materials include those based on biomass, e.g. lignin, or products of hydrothermal carbonization (HTC) or precipitation. Such materials have a lower carbon content compared to carbon black, but show interesting properties due to advanced functionalization.

[0003] Such HTC-based particulate materials can be produced, for example, by the methods described in WO2016 / 020383, DE10 2016 201 801 A1 or WO2017 / 085278. In the production of these HTC-based particulate materials, the adjustment of certain process parameters opens up the possibility of influencing, in particular, the resulting particle size distribution. The particle size distribution is usually measured by laser diffraction according to ISO 13320 or determined via multi-stage screening methods such as screening towers. In this way, the spatial extent of isolated particles is detected. Such particles are either agglomerates of much smaller primary particles that cannot or are not easily separable from one another, or they are isolated primary particles. If the particulate carbon material is at least partially an agglomerate, i.e. consisting of primary particles that cannot or are not easily separable, the size of these primary particles cannot be determined by measuring the particle size distribution. To account for the size of such agglomerated primary particles, the specific surface area of ​​the particulate carbon material is measured. The specific surface area is an indirect measure of the average size of primary particles that are isolated and cannot be separated or easily separated.

[0004] The specific surface area can be quantified, for example, by methods such as BET or STSA measurements, where the sum of the outer and inner surfaces is determined by BET measurements, whereas in STSA determination only the outer surface is determined. Suitable measurement methods are specified, for example, in ASTM D 6556-14.

[0005] It is known that the average size or amount of specific surface area of ​​the primary particles affects the properties of materials produced using particulate carbon materials, for example rubber products produced by compounding particulate carbon materials with elastomers and subsequent crosslinking. For example, the wear behavior of rubber products differs depending on whether particulate carbon materials with high or low BET surface areas are used. The same is true for mechanical properties such as tensile strength. Higher BET surface area values ​​correlate with higher tensile strength values ​​and lower wear. Here, when using HTC-based particulate carbon materials, a minimum of 15 m is required to obtain high-quality rubber products. 2 / g, preferably 20m 2 / g or more, preferably 30m 2 Specific surface area values ​​of 0.1 g or more are often required.

[0006] However, when producing particulate carbon materials by HTC or precipitation, the above mentioned possibilities for influencing the primary particle size (measured indirectly via the specific surface area) do not always result in the desired high specific surface area within commercially acceptable limits.

[0007] Surprisingly, through SEM imaging studies, it was found that the particulate carbon materials obtained by conventional techniques do not consist of primary particles that are homogenous in terms of their size.

[0008] For the separation of mixtures of materials of different sizes, classification methods such as screening, air classification or the float-sink process are suitable. With these methods, the separation of fractions is carried out with respect to size (sieving process) or size and / or specific material density (wind sifting, float-sink process). DE 28 29 977 discloses a method for classifying cement, for example. However, such methods are not suitable as prior art for the separation of particulate carbon material consisting of primary particles of different sizes into two batches which are more homogeneous with respect to primary particle size, because - primary particles are (at least partially) present in agglomerates, so that classification methods aimed at separating them with respect to size are unable to distinguish between large primary particles and agglomerates of substantially smaller primary particles of approximately the same size; - and because the intrinsic material density of primary particles of different sizes is the same. Thus, the prior art sorting methods do not provide a way to separate particulate carbon material into batches with different specific surface areas.

[0009] It is therefore desirable to provide a method that allows selective separation into fractions with different specific surface areas. For example, it would be possible to separate a fraction with a high surface area from a material with a relatively low specific surface area, which could be used for more demanding applications (while the fraction with the lower specific surface area would still be suitable for other applications). Thus, particulate carbon materials with a more homogeneous distribution of the specific surface area could also be obtained, which could be advantageous for certain applications. However, such a separation process is not known, particularly since it is easy to carry out. Summary of the Invention [Problem to be solved by the invention]

[0010] It is therefore an object of the present invention to disclose a method for providing a more homogenous fraction of the above-mentioned particulate carbon material.

[0011] This problem is solved by a method as defined in claim 1, a product as defined in claims 7, 8 and 11 and a use as defined in claim 10. Preferred embodiments and further aspects of the invention result from the further claims and the embodiments given in the detailed description below. [Brief description of the drawings]

[0012] [Figure 1] 1 shows a schematic representation of a possible embodiment of the method of the present invention; [Diagram 2] An embodiment is shown in which after the first separation in the powder separator, the two resulting fractions are dried and then each is further separated in a classifier. [Diagram 3] 3a and 3b show schematic process diagrams for a process design of separation according to FIG. 1 using a powder separator with and without recycle of the first fraction. [Figure 4] The wear values ​​of the example compounds are shown. [Diagram 5] The tensile strength values ​​of the compounds of the examples are shown. [Figure 6] The wear values ​​of the example compounds are shown. [Figure 7] The tensile strength values ​​of the compounds of the examples are shown. [Figure 8] 1 shows the stress-strain curve of the compound of Example 4. Detailed Description of the Invention

[0013] The method of the invention allows for a simple and targeted fractionation of particulate carbon materials obtained from precipitation or hydrothermal carbonization (hereinafter referred to as HTC) of carbon-containing starting materials, e.g. renewable raw materials such as wood, grass or straw, or materials derived therefrom, e.g. lignin, molasses, stillage, sugar or starch. HTC or precipitation embodiments are known to the skilled person, in particular such particulate carbon materials can be produced by methods such as those described in WO2006031175, WO2006038863, WO2009104995 (precipitation), WO2016 / 020383 or WO2017 / 085278 (HTC). The particulate carbon materials obtained by precipitation or HTC have a carbon content of at least 5 m. 2 / g, preferably at least 7m 2 / g, more preferably at least 9m 2 / g STSA surface area has been shown to be useful.

[0014] The STSA surface area of ​​the particulate carbon material before separation in the present invention is typically 5 to 200 m 2 / g, for example, 10 to 150 m 2 / g or 10~100m 2 / g, preferably 10 to 75 m 2 / g or 10~50m 2 / g, more preferably 10 to 40m 2 / g or 10~30m 2 / g. Such particulate carbon materials with particularly favorable STSA surfaces are easily obtained by HTC methods or precipitation and are promising with regard to the possibility of using the fraction obtained by the separation according to the invention. Typically, such particulate carbon materials comprise a commercially relevant particulate carbon material fraction having a STSA surface area higher than the average STSA of the particulate carbon material, suitable for use in high-value applications. At the same time, the STSA surface area of ​​the fraction having a lower STSA surface area than the average STSA of the particulate carbon material is still sufficiently large so that commercial exploitation is possible. In the case of particulate carbon materials, the values ​​of the STSA surface area and the BET surface area are not too far apart. As a result, the particulate carbon material is not porous or minimally porous. Advantageously, the BET surface area and the STSA surface area do not deviate from each other by more than 20%, preferably by more than 15%, particularly preferably by more than 10%.

[0015] The carbon content of the particulate carbon material (based on ash-free dry matter) is more preferably 50 to 80% by mass (Ma%), more preferably 60 to less than 80 Ma%. Thus, the particulate carbon material is a material with a carbon content different from that of carbon black. By producing the particulate carbon material by HTC or precipitation, the carbon content is reduced compared to carbon black, and therefore the content of functional groups on the particle surface is increased. This may be beneficial for the subsequent use of the particulate carbon material.

[0016] Surprisingly, it has been shown that it is possible to separate such particulate carbon materials by simple gravity separation into at least two fractions (first and second fractions) with significantly different specific surface areas (STSA surface areas), with one fraction (first fraction) exhibiting a specific surface area (STSA surface area) value higher than that of the starting material, and the other fraction (second fraction) exhibiting a specific surface area (STSA surface area) value lower or equal to that of the particulate carbon material.

[0017] The fractions obtained by the separation according to the invention are more homogeneous than the particulate carbon material, respectively, in terms of the distribution of the primary particle size. However, it has been shown that the separation does not significantly affect the particle size distribution (i.e. the size distribution of the aggregates). The fractions obtained after separation essentially correspond to those of the particulate carbon material.

[0018] Since such gravity separation is relatively simple in terms of equipment and less complicated in the control of the process, fractions from particulate carbon materials suitable for more demanding high quality applications can be obtained cost-effectively by this method without the need for more complicated process adaptations, for example, in HTC or precipitation. For example, fractions with significantly higher specific STSA surface areas can be separated from easier to produce particulate carbon materials from HTC and from precipitation with a relatively lower specific STSA surface area, which may, for example, command a higher price. Advantageously, these fractions with significantly higher STSA surface areas are used in applications where, for example, tensile strength and / or wear are important parameters.

[0019] Since such gravity separations can be carried out in both the liquid and gas phase, these separations can easily be combined with systems for HTC or precipitation. The basic process flow for this is shown in Figure 1. According to the invention, organic material, e.g. renewable raw materials such as wood, grass, straw, or substances derived from these such as lignin, molasses, stillage, sugar, starch, etc., are dissolved or fed mainly in solution in a first process step and are separated by HTC or precipitation into a volume of at least 5 m. 2 The particulate carbon material is converted to a particulate carbon material having an STSA of 10000000 / g. The particulate carbon material is then separated into at least two fractions in a second process step, gravity separation. In this context, the term liquid phase means that the particulate carbon material is present in a liquid medium, such as the water or aqueous phase used in the HTC or precipitation. Similarly, the term gas phase means that the particulate carbon material is present in a gaseous medium, such as air, nitrogen, superheated steam, carbon dioxide, or a mixture of these gaseous media.

[0020] Apparatuses for subjecting such phases to separation are well known to those skilled in the art. Examples include powder separators (liquid powder separators have been shown by the present invention to be suitable for separating particulate carbon materials dispersed in a liquid medium, such as water; powder separators can also be used for particulate carbon materials fluidized with a gas, such as air, nitrogen, superheated steam, carbon dioxide, or a mixture, and introduced into the powder separator), centrifuges (centrifuges have also been shown by the present invention to be suitable for separating particulate carbon materials dispersed in a liquid medium, such as water), or classifiers (air classifiers have been shown by the present invention to be suitable for separating particulate carbon materials fluidized with air, nitrogen, superheated steam, carbon dioxide, or a mixture, and introduced into the classifier). Figures 3a and b show an apparatus suitable for separation in a liquid powder separator. The particulate carbon material is recovered in a first process step from the organic material by precipitation or HTC and is fed to a second process step, for example together with water. There, it can be pumped, for example as a slurry with water, to a liquid powder separator to separate the second fraction, and the part not discharged as the second fraction can be returned to the vessel containing the original particulate carbon material, and the first fraction can be taken off after completion of the process (FIG. 3a). Alternatively, in a second process stage, the particulate carbon material can also be fed as a slurry with water to a liquid powder separator, where separation into a first and a second fraction takes place (FIG. 3b). Both the first and the second fraction can be fed to the next process step, either continuously or by a batch process. However, the invention is not limited to the use of these particular devices. All devices allowing separation according to the basic principles disclosed herein, as well as other classification devices, fluidized bed devices, centrifuges, etc. can be used.

[0021] According to the invention, different types of separation can also be combined. For example, since the particulate carbon material can be obtained from HTC or precipitation in an aqueous phase, the separation can first be carried out in a powder separator (e.g. a liquid powder separator). The fractions obtained can then be subjected to a further separation process, independently of each other, in the liquid or gas phase. Thus, at least one of the fractions obtained can then be further separated, for example after drying, in an air classifier. This option is shown diagrammatically in FIG. 2. The type of separation process is selected depending on the availability, the type of separation required (if fractions with very different values ​​for a particular STSA surface are required, or the differences should not be too pronounced, if fractions of approximately the same size are required, or if the separation results in at least one small but very uniform fraction, which may be combined with extremely different values ​​of the respective particular STSA surface), and economic considerations.

[0022] In this context, in the case of liquid phase separation (i.e. when using a slurry of particulate carbon material in an essentially liquid carrier, in particular an aqueous carrier), the proportion of particulate carbon material in the liquid phase is about 1-20% by weight (mass percent), preferably 5-15% by weight, in particular 6-10% by weight. Separation via a powder separator is then achieved by appropriately adjusting the pressure drop across the powder separator (e.g. a liquid powder separator) by adjusting the feed and discharge rates. The pressure drop is preferably 0.2-5 bar, more preferably 0.8-4 bar, in particular 1.5-3 bar. In the case of separation in the gas phase (i.e. essentially aerosol), the proportion of solids is about 0.01-0.5 kg / m 3 , preferably 0.05 to 0.4 kg / m 3 , especially 0.1 to 0.3 kg / m 3 It is.

[0023] Advantageously, the ratio of D(50) of the first fraction to D(50) of the second fraction is between 0.45 and 0.75, more preferably between 0.50 and 0.60. Advantageously, the ratio of D(90) of the first fraction to D(90) of the second fraction is between 0.5 and 0.8, more preferably between 0.6 and 0.7. Advantageously, the ratio of D(98) of the first fraction to D(98) of the second fraction is between 0.9 and 1.1, more preferably between 0.95 and 1.05. These ratios can be easily achieved by adjusting the conditions (ratio of particulate carbonaceous material, powder separator / sieve conditions, etc.), as shown in the examples. The values ​​of D(50), D(90) and D(98) are measured by laser diffraction according to ISO13320. Furthermore, the favorable ratio of values ​​of D(50), D(90), and D(98) demonstrates that particulate carbon materials behave significantly differently in gravity separation than conventional materials that are separated into different sized materials in gravity separation.

[0024] Advantageously, the ratio of the material density of the second fraction to the material density of the first fraction according to ISO 21687 is between 0.95 and 1.05, even more preferably between 0.975 and 1.025. Again, such a ratio can be achieved by adjusting the process parameters. Moreover, from the advantageous ratio of material densities it is again clear that the particulate carbon material behaves significantly differently in gravity separation than materials that are suitable for gravity separation for separating materials of different densities according to the prior art.

[0025] It has been shown to be particularly advantageous if the separation in the gas phase is followed by comminution or deagglomeration in a mill, for example a jet mill. For this purpose, the gas loaded with particulate carbon material is first fed to a powder separator, where the second fraction is separated (together with a small part of the gas). The gas, now loaded only with the first fraction, is dedusted in a filter, where the first fraction is separated. The combination of comminution and subsequent gravity separation applied to the particulate carbon material has the advantage that the above-mentioned ratio of D(90) to D(98) ensures that mainly coarse particles are not removed in the powder separator, and that the filter is loaded mainly with fine particles. This ensures that the filter effect is not impaired by excess fines. Advantageously, therefore, a process for separating particulate carbon feedstock, where the particulate carbon feedstock has been obtained by hydrothermal carbonization or precipitation of an organic feedstock, where the particulate carbon feedstock is separated from the powder separator by a pressure of at least 5 m 2 / g, and after grinding into at least two fractions, a first fraction is separated in a filter and has an STSA surface area greater than the STSA surface area of ​​the particulate carbon material, and a second fraction is separated in a powder separator and has an STSA surface area less than the STSA surface area of ​​the particulate carbon material, the method including gravity separation of the particulate carbon material.

[0026] Moreover, it has been shown to be particularly advantageous if the separation in the gas phase is followed by a drying step, for example in a fluidized bed dryer, spray dryer, entrained bed dryer or drum dryer. For this purpose, the gas, which has undergone a drying step and is loaded with particulate carbon material, is first fed to a powder separator, where the second fraction is separated (together with a small part of the gas). Now, the gas, which is loaded only with the first fraction, is dedusted in a filter, where the first fraction is separated. The combination of drying applied to the particulate carbon material and subsequent gravity separation has the advantage that the above-mentioned ratio of D(90) to D(98) ensures that mainly coarse particles are not removed in the powder separator, while the filter is loaded mainly with fine particles. This ensures that the filter effect is not impaired by excess fines. Advantageously, therefore, is a process for separating particulate carbon feedstock, where the particulate carbon feedstock has been obtained by hydrothermal carbonization or precipitation of an organic feedstock, where the particulate carbon feedstock is at least 5 m 2 / g, and after grinding into at least two fractions, a first fraction is separated in a filter and has an STSA surface area greater than the STSA surface area of ​​the particulate carbon material, and a second fraction is separated in a powder separator and has an STSA surface area less than the STSA surface area of ​​the particulate carbon material, the method including gravity separation of the particulate carbon material.

[0027] The method according to the invention results in fractions of particulate carbon material that differ in terms of STSA surface area. However, as already explained and shown in the examples, these fractions do not differ significantly from each other and from the particulate carbon material in terms of their particle size distribution. However, since fractions with different STSA surface areas are separated, each fraction is more homogeneous in terms of STSA surface area. Thus, the invention provides the option to separate a fraction with a high STSA surface area from a particulate carbon material with a low STSA surface area, which can be used in more demanding applications. In contrast, a fraction with a low STSA surface area can be separated from a starting material with a high STSA surface area, so that the STSA surface area is further increased in the remaining fraction.

[0028] Taking into account the process control variants disclosed herein, these fractions and their STSA surface areas can be selectively obtained, since it will be clear to the skilled person how to take into account the STSA surface area of ​​the particulate carbon material. The yield and / or STSA surface area of ​​the target fraction can be obtained depending on the degree of separation. The STSA surface area of ​​the fractions provided according to the invention, in particular the first fraction, is preferably at least 5% greater than the STSA surface area of ​​the particulate carbon material, in an embodiment at least 10% greater, in some cases at least 20% greater, particularly preferably at least 30% greater. At the same time, the first fraction is more homogeneous with respect to its composition (in particular with respect to the distribution of primary particle sizes) than the particulate carbon material. The STSA surface area of ​​the fractions provided according to the invention, in particular the first fraction, is preferably at most 200%, in an embodiment at most 175%, in some cases at most 150% greater than the STSA surface area of ​​the particulate carbon material. Preferably, the first fraction is at least 15 m 2 / g, more preferably at least 20m 2 / g, more preferably at least 30m 2 / g or more. Preferably, the first fraction is used in demanding applications, such as tire treads, preferably pneumatic tires, conveyor belts where low wear is a requirement, or tire sidewalls, such as pneumatic tires where tensile strength is a requirement.

[0029] Advantageously, gravity separation can also be used as a method for adjusting the STSA of the first or second fraction. This ensures that even if the STSA of the particulate carbon material changes over time, at least one of the fractions obtained by gravity separation has an STSA that changes only within a defined tolerance range. Instead of STSA, BET or particle size distribution can also be used as an indirect measure of STSA. For this purpose, for example, the STSA, BET or particle size distribution of the first or second fraction are measured periodically and the process parameters of the gravity separation are adjusted so that the STSA, BET or particle size distribution of the first or second fraction changes only within a defined tolerance range. In the case of gravity separation in the gas phase, this can be done, for example, by adjusting the speed of the classifier wheel or by adjusting the volumetric flow rate of the gas. In the case of gravity separation in the liquid phase, this can be done, for example, by adjusting the volumetric flow rate of the liquid or the pressure drop in the separation device (for example, a powder separator).

[0030] Advantageously, the tolerance range is a maximum of 110% and a minimum of 90% of the target value of STSA, BET, or particle size distribution of the first or second fraction. Advantageously, the tolerance range is +5m of the target value of STSA or BET of the first or second fraction. 2 / g, minimum is -5m 2 / g.

[0031] In the method according to the present invention, the weight ratio of the first fraction to the second fraction (each for the separation operation) can be set to 1:15 to 15:1, for example, 1:10 to 10:1. The above ratio can be changed depending on the separation type, and separation at 1:5 to 5:1, for example, 1:2 to 2:1 is also possible.

[0032] The present invention also relates to a particulate carbon material having a uniform distribution of primary particles, which is advantageously produced by the method according to the invention.

[0033] In such a particulate carbon material having a uniform distribution of primary particles, the ratio of measured STSA to calculated STSA is preferably 0.7 to 1.3, more preferably 0.75 to 1.25, more preferably 0.8 to 1.2, more preferably 0.85 to 1.15, and more preferably 0.9 to 1.1. The calculated STSA is calculated using the following formula: 1.STSA surface area = sphere surface area / (sphere volume * material density) 2. Surface of sphere = PI * measured diameter of sphere^2 3. Volume of sphere = 1 / 6*PI*measured diameter of sphere^3 Substituting 2 and 3 into 1, we get the following equation: Surface area of ​​STSA = 6 / (measured sphere diameter * material density) The measured sphere diameter is the average diameter of the smallest isolated primary particles visible in the SEM image.

[0034] Furthermore, the present invention also provides the uses defined in the claims, as well as elastomeric compounds and products made therefrom, such as tires, pneumatic tires and other products (in vulcanized and non-vulcanized form) made from these elastomeric compounds. However, the materials obtained or provided according to the present invention can also be used in other material compositions, such as thermoplastic or liquid materials, such as paints, ink compositions, etc. Here, the materials obtained or provided according to the present invention contribute to improving the mechanical properties, but can also be used for other purposes, such as coloring, providing chemical functionalities (due to functional groups present in or on the particles). EXAMPLES

[0035] Example 1 According to the process description in WO2017 / 085278, the STSA is 11.9m 2 / g of particulate carbon material was obtained by the first process step. The obtained particulate carbon material was separated into a first fraction and a second fraction by gravity separation in the gas phase in three different process steps according to the main principles shown in Figure 1.

[0036] For gravity separation, a Hosokawa Alpine Picoline air classifier equipped with a classifier wheel was used. A picosplit (20 ATP classifier) ​​and a picojet (40 AFG fluidized bed counter jet mill) module were used. The feed material was metered by a micrometering device (PMD) associated with the picoline. The yields obtained and the STSA surface areas determined for the fractions are shown in Table 1. [Table 1]

[0037] The particulate carbon material and the two fractions were then ground in a jet mill to a particle size of D99<10 μm. All three materials were mixed into an SBR matrix as fillers. After vulcanization, stress-strain curves were recorded in a tensile test. The tensile strength results are shown in Figure 5. Additionally, wear was measured. The results are shown in Figure 4.

[0038] This experiment demonstrated that a simple gravity separation process allowed the separation of the STSA surface area to be fairly small (11.9 m 2 It impressively shows that valuable and substantial fractions with significantly higher STSA surface areas can be obtained from materials with a STSA surface area of ​​0.1 g / g. In this connection, it is possible to specifically adjust the respective yield or achievable STSA surface area (see Table 1, experiments 1-3). According to the invention, it is possible to separate fractions with very low STSA surface areas from materials with an already high STSA surface area (i.e. particles with STSA surface areas that are considered insufficient in practice for highly demanding elastomer compounding applications requiring high abrasion resistance and high wear resistance, see Table 2). The property profile of the fractions with increased STSA surface obtained by separating the fractions with low STSA surface is improved, since on the one hand a more homogeneous fraction is obtained in terms of STSA surface and on the other hand a fraction with inferior properties (with respect to elastomer applications) is separated. Example 2

[0039] According to the process description in WO2017 / 085278, STSA is 46m 2 / g of particulate carbon material was obtained by the first process step. The obtained particulate carbon material was separated in the experiment by gravity separation in liquid phase into a first and a second fraction (see Table 2) according to the main principles shown in Figure 1.

[0040] 33m 2 Another particulate carbon material having an STSA of 1000 / g was obtained in the first process step. The particulate carbon material was separated into a first and a second fraction in the experiment by gravity separation in the liquid phase. The STSA surface areas of the obtained fractions and their respective yields are shown in Table 2. [Table 2]

[0041] A powder separator was used for gravity separation. The basic setup of the equipment is shown in Figure 3a. Organic material was converted to particulate carbon material by HTC in the first process step and fed to the second process step together with water, buffered in a vessel (B). The mixture of water and particulate carbon material was continuously removed from the vessel (B) by a pump (A) and separated into two fractions in a liquid-powder separator (C). The volumetric flow rate removed from the vessel (B) by the pump (A) is adjusted so that the pressure drop (p) across the liquid-powder separator (C) reaches a certain value. The pressure drop is determined between the inlet and the outlet of the liquid-powder separator. The concentration of particulate carbon material in the water ranged from 5Ma.% to 10Ma.% (average was 8.6Ma.%).

[0042] The particulate carbon material and the two fractions were then ground in a jet mill to a particle size of D99<10μm. All three materials were mixed into an SBR matrix as fillers. After vulcanization, stress-strain curves were recorded in a tensile test. The tensile strength results are shown in Figure 6. Additionally, the wear was measured. The results are shown in Figure 7.

[0043] Compounds and vulcanizates for the elastomeric compounds of Examples 1 and 2 were prepared according to the following formulations using the following process: [Table 3]

[0044] The mixture was prepared according to the following procedure: The mixtures were prepared using a Haake Rheomix 3000 measuring kneader (tangential rotor geometry) at a filling rate of 70%. The mixing temperature was kept constant by speed control. The mixing time was approximately 20 minutes. Vulcanization was carried out at 160 °C according to the optimal t90 time determined by rheometer plus 1 min per mm of sheet thickness. Example 3

[0045] STSA is 13.1m 2 Particulate carbon material with a carbon content of 0.01g / g was obtained in the first process step. In the experiments, the primary particulate carbon material was separated into a first and a second fraction by gravitational separation in the gas phase in a powder separator. The particulate carbon material was first fed to a jet mill equipped with a classifying wheel and ground. A 100AFG jet mill was used (nozzle insert 1.9 mm). A D20 T36 GLATT TR5; slot; RA(l)=1.2 was used as the classifying wheel. The crushed material passed through the classifying wheel and was then fed to the powder separator. From the powder separator, the first fraction was discharged with the air flow and separated from the air flow via a filter, while the second fraction was directly separated in the powder separator. In this way, a 6.3m 3 At an air flow rate of 1.0 g / h, 0.15 kg of the first fraction and 0.85 kg of the second fraction were obtained from 1 kg of granular carbon material. The results are shown below. [Table 4]

[0046] For both fractions the particle size distribution was determined by laser diffraction and is shown below. [Table 5]

[0047] It was shown that the separation of the particulate carbonaceous material did not significantly alter the particle size distribution, despite the different values ​​of specific surface area present after separation: both fractions showed good agreement of particle size distribution.

[0048] The two fractions thus obtained (fraction 1 and fraction 2) were mixed as fillers into an EPDM matrix. After vulcanization, stress-strain curves were recorded in tensile tests. The results are shown in Figure 8. [Table 6]

[0049] The mixture was prepared according to the following procedure: The mixtures were prepared using a W&P type GK1.5E mixer (cross-reversing rotor geometry) at a filling rate of 70%, a mixing temperature of 40 °C, and a speed of 40 rpm. Vulcanization was carried out at 160 °C according to the optimal t90 time determined by the rheometer plus 1 min per mm of sheet thickness. Example 4

[0050] Several samples of particulate carbon material, as well as isolated samples Q and R of Example 3 according to the method of the present invention, were measured for STSA and analyzed by SEM. For each sample, the average diameter of the smallest isolated primary particle was determined by SEM. From this, the STSA was calculated. The measured STSA correlated with the calculated STSA. The results are shown in Table 5. [Table 7]

[0051] Here, it was found that there was a more significant correlation between the calculated and measured surface values ​​for the samples according to the invention compared to the starting material, again indicating the homogeneity of the material obtained by the method of the invention.

Claims

1. 1. A method for separating a particulate carbon feedstock obtained by hydrothermal carbonization or precipitation of an organic feedstock into at least two fractions, comprising the steps of: The particulate carbon material has an STSA surface area of ​​at least 5 m 2 / g, the STSA surface area of ​​the first fraction is greater than the STSA surface area of ​​the particulate carbon material; the STSA surface area of ​​the second fraction is less than the STSA surface area of ​​the particulate carbon starting material; A method comprising gravity separation of particulate carbon material.

2. 13. The method according to at least one of the preceding claims, wherein the gravity separation is carried out in the liquid or gas phase.

3. 2. The method of claim 1, wherein gravity separation is used to adjust the STSA of the first fraction or the second fraction.

4. 10. The method according to at least one of the preceding claims, wherein the STSA surface area of ​​the first fraction is at least 5% greater than the STSA surface area of ​​the particulate carbon feedstock.

5. 10. The method according to at least one of the preceding claims, wherein the weight ratio of the first fraction to the second fraction is in the range of 1:10 to 10:

1.

6. 10. The method according to at least one of the preceding claims, wherein the gravity separation is carried out in an air classifier or a powder separator.

7. 13. The method according to at least one of the preceding claims, wherein the particulate carbon feedstock has a carbon content of 55 Ma% or more and less than 80 Ma%.

8. A particulate carbon material having a uniform distribution of primary particles, wherein the ratio of measured STSA to calculated STSA is 0.7 to 1.3, more preferably 0.75 to 1.25, more preferably 0.8 to 1.2, more preferably 0.85 to 1.15, more preferably 0.9 to 1.

1.

9. 2. Particulate carbon material with homogeneous distribution, obtainable by a method according to at least one of the preceding claims.

10. 10. A particulate carbon material having a uniform distribution as described in claim 8 or 9, wherein the STSA surface area is at least 5% greater than the STSA surface area of ​​the particulate carbon starting material and / or the STSA surface area of ​​the first fraction is at least 50% greater than the STSA surface area of ​​the second fraction.

11. STSA surface area is at least 15 m 2 11. The particulate carbon material having a uniform distribution according to claim 8, wherein the carbon content is 1 / g.

12. STSA surface area is at least 20 m 2 11. The particulate carbon material having a uniform distribution according to claim 8, wherein the carbon content is 1 / g.

13. STSA surface area is at least 30 m 2 11. The particulate carbon material having a uniform distribution according to claim 8, wherein the carbon content is 1 / g.

14. Use of the particulate carbon material with homogeneous distribution according to at least one of claims 8 to 13 or obtainable by the method according to at least one of claims 1 to 6 as a filler in elastomers, thermoplastics, paints, lacquers, in particular in elastomers and thermoplastic elastomers.

15. 14. A rubber product comprising a particulate carbon material with a homogeneous distribution according to at least one of claims 8 to 13 or obtainable by the method according to at least one of claims 1 to 6.

16. The particulate carbon material is at least 15 m 2 16. The use according to claim 14 or the product according to claim 15, having an STSA of 0.1% by weight / g.

17. 17. The use or product according to any one of claims 14 to 16, which is the tread or sidewall of a pneumatic tire.

Citation Information

Patent Citations

  • Monodisperse spherical carbon porous body

    JP2006219322A